1994
DOI: 10.1523/jneurosci.14-04-02313.1994
|View full text |Cite
|
Sign up to set email alerts
|

AMPA-induced excitotoxic lesions of the basal forebrain: a significant role for the cortical cholinergic system in attentional function

Abstract: The aim of the present study was to clarify the role of the basal forebrain (BF)-cortical cholinergic system in visual attentional function by investigating the effect of alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA)-induced lesions of the basal forebrain on performance of a five-choice serial reaction time task. AMPA lesions in the present study produced a profound effect on performance of the task, as measured by choice accuracy and correct response latency. This deficit was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
233
1
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(250 citation statements)
references
References 32 publications
14
233
1
2
Order By: Relevance
“…Other brain regions that have important significance in correct performance of the 5-CSR task include the anterior cingulate cortex, striatum and the thalamus (Muir et al, 1994;Muir et al, 1996;Rogers et al, 2001;Robbins, 2002;Chudasama et al, 2003) Baviera et al, (2008) used the competitive NMDA receptor antagonist 3-(R)-2-carboxypiperazin-4-propyl-1-phosphonic acid (CPP), which was injected directly into the mPFC of male Lister Hooded rats (50 ng/side) trained in the 5-choice task. This experiment demonstrated that selective blockade of NMDA receptors specifically located within the mPFC produced a profound impairment in the rat's ability to perform in the task.…”
Section: -Choice Serial Reaction Time Taskmentioning
confidence: 99%
“…Other brain regions that have important significance in correct performance of the 5-CSR task include the anterior cingulate cortex, striatum and the thalamus (Muir et al, 1994;Muir et al, 1996;Rogers et al, 2001;Robbins, 2002;Chudasama et al, 2003) Baviera et al, (2008) used the competitive NMDA receptor antagonist 3-(R)-2-carboxypiperazin-4-propyl-1-phosphonic acid (CPP), which was injected directly into the mPFC of male Lister Hooded rats (50 ng/side) trained in the 5-choice task. This experiment demonstrated that selective blockade of NMDA receptors specifically located within the mPFC produced a profound impairment in the rat's ability to perform in the task.…”
Section: -Choice Serial Reaction Time Taskmentioning
confidence: 99%
“…Ach is an important neuromodulator in the cerebral cortex. It has been implicated in Many important brain functions, such as arousal (Celesia & Jasper, 1966), attention (Muir et al, 1994; for a review see Saner & Bruno, 2000) and sensory discrimination (Jacobs & Juliano, 1995). It is projected from the nucleus basalis of the basal forebrain (Eckenstein· et al, 1988;Mesulam et al, 1983;Mesulan & Van Hoesen, 1976) and terminates diffusely tbroughout the cerebral cortex.…”
Section: Acetylcholinementioning
confidence: 99%
“…On the basis of the effects of nonselective neurotoxic and electrolytic lesions of basal forebrain nuclei, distinct functions have been proposed for cholinergic projections to the neocortex and hippocampus. The cholinergic neurons that project to neocortex are thought to be involved primarily in the regulation of attentional function (Robbins et al, 1989;Muir et al, 1992Muir et al, , 1994Voytko et al, 1994), whereas cholinergic basal forebrain neurons projecting to the hippocampus are thought to play an important role in learning and memory (Hagan et al, 1988;Kelsey and Landry, 1988;Decker et al, 1992;Kelsey and Vargas, 1993).…”
Section: Inhibition; Alzheimer's Diseasementioning
confidence: 99%
“…Attentional disruption produced by nonselective neurotoxic basal forebrain lesions (Chiba et al, 1994;Muir et al, 1994;Voytko et al, 1994) also is apparent after selective cholinergic lesions of the basal forebrain (Chiba et al, 1995(Chiba et al, , 1997J. J. Waite, personal communication).…”
Section: Inhibition; Alzheimer's Diseasementioning
confidence: 99%